Mineral Composition of a Reserve Forest Soil - Pandit, B R; Thampan, S (Annals of Arid Zone, 2016)
Soil samples collected from varying depths in Victoria Park Reserve Forest near Bhavnagar (Gujaral) in three different seasons were analysed for determining phosphorus calcium, magnesium, nitrogen and carbon contents. The soil was clayey but poor in mineral status. It was alkaline and the pH decreased from upper to lower layers at 30, 40 and 50 cms from summer to monsoon and winter. pH also varied in different seasons at the same depths. With a decrease in the pH there was an increase in phosphorus, calcium and magnesium in the soils of same depths from summer to winter. Nitrogen; however, decreased with the fall in pH. Carbon content was highest during summer.